An in vivo spectrophotometric evaluation of Vivera® and Essix® clear thermoplastic retainer discolouration - Zafeiriadis Anastasios A; Karamouzos Andreas; Athanasiou Athanasios E; Eliades Theodore; Palaghias George (Sciendo, 2018)
To assess the in vivo colour alterations of two different clear thermoplastic retainers.